Infecção pelo Trypanosoma cruzi em doadores de sangue: Revisão Sistemática da Literatura e Estudo de Prevalência no Hemocentro de Goiás - SANTOS, Cristiane Araújo Tuma (2011)
Introduction: Chagas disease or American trypanosomiasis is one of several infectious diseases that can be transmitted via blood, justifying the rigorous screening of blood donors. The transfusion transmission of trypanosomiasis has been reduced in Brazil with the implementation of programs to control the quality of blood products. Objectives: a) To do Systematic Review addressing the issue of transfusion transmission of Chagas disease and b) determine the prevalence of Chagas' infection in blood donors attending the Coordinator Blood Bank of Goiás, regional blood centers of Catalão, Rio Verde and Jataí and mobile units that collect blood in 62 cities in Goiás, in the years 2005 to 2009. Methods: 1) Systematic Review using the keywords "Chagas' disease," "blood donor", "Trypanosoma cruzi" and "blood transfusion" and the qualifier "epidemiology" in databases: MEDLINE, LILACS PAHO and WHOLIS. 2) Cross-sectional study to determine the seroprevalence for Trypanosoma cruzi, using data from computerized laboratory files whose serological technique was immunosorbent assay (ELISA). The positive donors were characterized by sex, age, nationality and origin, through records of attendance. Confidence Intervals were calculated at 95%. To reach statistical significance was considered p <0.05. Results: There were 314 articles in different databases, with 48 included in the analysis. We analyzed 210,890 records of donations during the period January 2005 to December 2009. 653 were found positive for T. cruzi, resulting in a prevalence of 0.30%. Among the donors with positive serology for T. cruzi, 69.22% were men and 30.78% were women. Most donors was born in Goiás (53.45%). The prevalence of infection in new donors was 1.27% while in return donors was 0.02%. Conclusions: Advances in Hemoterapy practice in Latin America and effective vector control decreased dramatically in recent decades the occurrence of transfusion Chagas disease in endemic areas. But, because it is not restricted geographically, this disease represents a significant challenge to the developed countries that receive large numbers of immigrants, which can transmit the disease through blood transfusions. The prevalence of positive donors at the Coordinator Blood Bank and Regional transfusion centers of Goiás trend shows decline when compared with previous studies.